Case report: A novel TLK2 variant with a neuropsychiatric phenotype from a Chinese family - Huang, Hongmei; Qian, Yue; Yang, Chenlu; Li, Shijie (Frontiers in Genetics, 2024)
Background: Tousled-like kinase 2 (TLK2) gene variants related neurodevelopmental disorder was recently described. The haploinsufficiency of TLK2 was considered as the most likely underlying disease mechanism, leading to a consistent neurodevelopmental phenotype. So far, only four studies, 49 patients from North America and Europe have been reported.In this study, we reported a Chinese family with TLK2-related neuropsychiatric phenotype. The proband, a two years and six months old boy presented with temper tantrums, mood lability, aggressiveness, congenital astigmatism and distinctive facial dysmorphism. Whole exome sequencing identified a novel heterozygous variation of TLK2 gene (c.49dupG, p.E17Gfs*10) in them. His father carried the same TLK2 gene variant, and exhibited anxiety and irritability. The parental grandparents and other family members had no such variation. Moreover, the proband was found to have global developmental delay, autism-like symptom and mild elevated homo-vanillic acid (HVA) and 2,3-dihydroxy-2-methylbutyric acid level tested in urine.Conclusions: Herein, we identified a novel TLK2 variant from a Chinese family and reported a new neuropsychiatric phenotype. This study also expanded the genotype profile of the newly defined TLK2-related neurodevelopmental disorder.